mRNA GPR162 changes are associated with decreased food intake in rat, and its human genetic variants with impairments in glucose homeostasis in two Swedish cohorts - Caruso, Vanni (2016)
G protein-coupled receptors (GPCRs) are a class of integral membrane proteins mediating intercellular interactions of fundamental physiological importance for survival including regulation of food intake, blood pressure, and hormonal sensing signaling, among other roles. Homeostatic alterations in the physiological status of GPCRs are often associated with underlying causes of disease, and to date, several orphan GPCRs are still uncharacterized.Findings from our previous study demonstrate that the Rhodopsin family protein GPR162 is widely expressed in GABAergic as well as other neurons within the mouse hippocampus, whereas extensive expression is observed in hypothalamus, amygdala, and ventral tegmental area, regions strictly interconnected and involved in the regulation of energy homeostasis and hedonic feeding.In this study, we provide a further anatomical characterization of GPR162 in mouse brain via in situ hybridization as well as detailed mRNA expression in a panel of rat tissues complementing a specie-specific mapping of the receptor. We also provide an attempt to demonstrate a functional implication of GPR162 in food intake-related behavior via antisense knockdown studies. Furthermore, we performed human genetic studies in which for the first time, variants of the GPR162 gene were associated with impairments in glucose homeostasis.